The Influence of Social Media and Facilities on Participants' Decisions to Participate in the Competition at the 2025 Medan Culinary Festival - Swastika Ziliwu; Suri Purnami (CV. Civiliza Publishing, 2025)
The MICE (Meetings, Incentives, Conventions, and Exhibitions) and culinary events industry are strategic sectors that play an important role in the development of tourism and the creative economy in Indonesia, especially in Medan. In today's digital era, social media has a crucial role in influencing consumer behavior and public participation in various events, including culinary competitions. In addition, the availability of adequate facilities is also a determining factor in the comfort and decision of participants to participate in the event. This study aims to determine the influence of social media and facilities on the decision of participants to participate in the competition at the CLEO Culinary Festival Medan 2025. The research method used is quantitative with a survey approach, where data is collected through a questionnaire distributed to 100 competition participants. Data analysis was carried out using multiple linear regression with the help of the SPSS version 25 program. The results showed that social media had a positive and significant effect on participants' decisions with a t????count value of 4.895 (p = 0.000). Facilities also had a positive and significant effect with a t????count of 4.590 (p = 0.000). Simultaneously, these two variables had a significant influence on participants' decisions with a value of F????count of 49.069 (p = 0.000) and an Adjusted R Square value of 0.493, which means that 49.3% of the variation in participants' decisions can be explained by social media and facilities. Social media and adequate facilities are key factors to increase participant participation and satisfaction in the CLEO Culinary Festival Medan 2025. Therefore, organizers are advised to continue to optimize social media strategies and improve the quality of facilities to support the success of the event.